2014
DOI: 10.7205/milmed-d-13-00289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Training Patterns on Injury Incidences in 12 Swiss Army Basic Military Training Schools

Abstract: Non-battle injury rates are a major health problem in the armed forces today. Injury rates are related to physical demands of daily military routine. The aim of this study is to investigate the impact of different physical training patterns on incidences of injuries in 12 Swiss Army basic military training schools. Therefore, injury data of 1,676 voluntary participant recruits and objective sensor data on physical demands of 50 volunteers at each of 12 trainings schools were assembled. Multiple linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Gradual onset injuries of the lower leg, particularly medial tibial stress syndrome, were the most common injury type in this study, concordant with rates observed in foreign armies (Kaufman et al, 2000, Schwartz et al, 2014. Therefore, recommendations for training modification in an attempt to reduce gradual onset injuries should be considered for future BMT in the studied population (Kaufman et al, 2000;Wyss et al, 2014).. Such modifications may include gradual running distance increments and night rest to reduce injury risk (Wyss et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Gradual onset injuries of the lower leg, particularly medial tibial stress syndrome, were the most common injury type in this study, concordant with rates observed in foreign armies (Kaufman et al, 2000, Schwartz et al, 2014. Therefore, recommendations for training modification in an attempt to reduce gradual onset injuries should be considered for future BMT in the studied population (Kaufman et al, 2000;Wyss et al, 2014).. Such modifications may include gradual running distance increments and night rest to reduce injury risk (Wyss et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, recommendations for training modification in an attempt to reduce gradual onset injuries should be considered for future BMT in the studied population (Kaufman et al, 2000;Wyss et al, 2014).. Such modifications may include gradual running distance increments and night rest to reduce injury risk (Wyss et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Training monotony has been used as injury risk index for more than a decade 10 11. For the above-mentioned reasons, in order to better understand the relationship between TL and injury risk, caution should be taken with the use of rolling averages and instead other more appropriate TL modelling could be used in everyday practice and research.…”
mentioning
confidence: 99%
“…9.1% of MD has been attributed to training MSKI within the ITC [3] with as much as 30-50% of disability cases with associated compensation costs of up to $1.5 billion have been attributed to MSKI in the US military [24]. Average medical costs per training related MSKI have been reported by Swiss military insurance as 1,750 (CHF) or 1,925 US $ equating to 6.9 million CHF or $7.6 m for 25,000 army recruits per year [25]. In addition, the complex bio-psycho-social implications of these injuries inevitably mean that the true financial cost is likely to be underestimated.…”
Section: Financial Implicationsmentioning
confidence: 99%